2022
DOI: 10.3390/ijerph19127125
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Three-Year Swim Training on Cardio-Respiratory Fitness and Selected Somatic Features of Prepubertal Boys

Abstract: The data regarding somatic and physiological effects of sport-related physical activities in youth are limited. Moreover, whether exercise training is capable of increasing cardio-respiratory fitness remains a disputable issue. The study undertook to assess the effect of swimming training on cardio-respiratory fitness (CRF) and the development of physical traits in prepubertal boys, and to determine which of the traits is the best predictor of their CRF. Forty 10-year old prepubertal boys (10.5 ± 0.3 y) were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…According to the studies reviewed by Baquet et al [34], endurance training improves aerobic capacity in children and adolescents by just 5-6%, or 8-10% when only studies finding its effect to be significant are considered. In our earlier research on the influence of a 3-year swimming training program on prepubertal boys, a 2-factor ANOVA of the 20-mSRT results (factor I: controls-swimmers; factor II: time) showed that the main group effect was statistically significant, but measurements taken at successive time points did not reveal statistically significant differences between the 2 groups [35]. It is likely that a similar situation also occurred in this study (the swimmers performed statistically insignificantly better on the 20-mSRT), but whether it was really so cannot be confirmed without longitudinal studies.…”
Section: Discussionmentioning
confidence: 80%
“…According to the studies reviewed by Baquet et al [34], endurance training improves aerobic capacity in children and adolescents by just 5-6%, or 8-10% when only studies finding its effect to be significant are considered. In our earlier research on the influence of a 3-year swimming training program on prepubertal boys, a 2-factor ANOVA of the 20-mSRT results (factor I: controls-swimmers; factor II: time) showed that the main group effect was statistically significant, but measurements taken at successive time points did not reveal statistically significant differences between the 2 groups [35]. It is likely that a similar situation also occurred in this study (the swimmers performed statistically insignificantly better on the 20-mSRT), but whether it was really so cannot be confirmed without longitudinal studies.…”
Section: Discussionmentioning
confidence: 80%
“…Swimmers are known to train for hours and cover kilometers daily, regardless of their race distances, and it is a well-established fact that many Olympic champions hold world records in various distances. Due to its horizontal position in the water and the unique technique of responding to buoyancy, gravity, and resistance in the water, as well as the different breathing techniques compared to outdoor sports, swimming is evaluated separately from other sports [3]. Physiologically, it is known that swimming is influenced by lower body fat, broader shoulders and hips, longer stroke length, shorter forearms, and wider arm circumference [4].…”
Section: Introductionmentioning
confidence: 99%
“…As swimming is a competitive event dominated by physical strength, the interaction between athletes' technical actions and the water in the swimming pool makes the body stay still or move in the water. 3 Therefore, the essence of motion is explained through the principle of motion. We need to use the most scientific methods to develop scientific training methods to improve athletes' project performance.…”
Section: Introductionmentioning
confidence: 99%